PQ Strategies in Monopolistic Competition: Some Insights from the Lab - Tiziana Assenza; Jakob Grazzini; Cars Hommes; Domenico Massaro (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2014)
We present results from 50-rounds experimental markets in which firms decide repeatedly both on price and quantity of a perishable good. The experiment is designed to study the price-quantity setting behavior of subjects acting as firms in monopolistic competition. In the implemented treatments subjects are asked to make both production and pricing decisions given different information sets. We investigate how subjects decide on prices and quantities in response to signals from the firms' internal conditions, i.e., individual profits, excess demand, and excess supply, and the market environment, i.e., aggregate price level. We find persistent heterogeneity in individual behavior, with about 46% of market followers, 28% profit-adjusters and 26% demand adjusters. Nevertheless, prices and quantities tend to converge to the monopolistically competitive equilibrium and we find that subjects' behavior is well described by learning heuristics.
Keywords: 330; Laboratory Experiments; Price-Quantity Competition; Monopolistically Competitive markets